Quantitative absorptive micro-sampling for decentralized monitoring of insulin-like growth factor 1 - Li, Xiaogang; Zhao, Zeqing; Chen, Shi; Guo, Ye; Pan, Hui; Yang, Xiao (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThis study establishes a novel quantitative acoustic mass spectrometry (QAMS) methodology for insulin-like growth factor 1 (IGF-1) detection.MethodsChromatographic separation utilized a Peptide C18 column (1.8 μm, 50 mm) with 0.1% formic acid/acetonitrile gradient elution, coupled to tandem mass spectrometry operated in scheduled multiple reaction monitoring (sMRM) mode.ResultsThe method demonstrated a lower limit of quantification (LOQ) of 10 ng/mL with linear dynamic range spanning 10-500 ng/mL. Comparative analysis of 74 paired plasma specimens revealed strong inter-matrix correlation with quantifiable bias.DiscussionThese advancements position QAMS- as a robust tool for decentralized IGF-1 monitoring, particularly valuable in pediatric growth disorder studies and resource-limited settings. Longitudinal stability validation and isoform differentiation remain focal points for future optimization.